A rolled-up-based fabrication method of 3D helical microrobots - Wang, Zihan; Mu, Xueliang; Tan, Liyuan; Zhong, Yukun; Cheang, U. Kei (Frontiers in Robotics and AI, 2022)
While the potential of using helical microrobots for biomedical applications, such as cargo transport, drug delivery, and micromanipulation, had been demonstrated, the viability to use them for practical applications is hindered by the cost, speed, and repeatability of current fabrication techniques. Hence, this paper introduces a simple, low-cost, high-throughput manufacturing process for magnetic helical microrobots with consistent dimensions. Photolithography and electron-beam (e-beam) evaporation were used to fabricate 2D parallelogram patterns that were sequentially rolled up into helical microstructures through the swelling effect of a photoresist sacrificial layer. Helical parameters were controlled by adjusting the geometric parameters of parallelogram patterns. To validate the fabrication process and characterize the microrobots’ mobility, we characterized the structures and surface morphology of the microrobots using a SEM and tested their steerability using feedback control, respectively. Finally, we conducted a benchmark comparison to demonstrate that the fabrication method can produce helical microrobots with swimming properties comparable to previously reported microrobots.